Roles of Replication Protein A (RPA) in DNA Metabolism - Narendra Kumar; Anamica; Everest Shiwach; Sandeep Kumar; Suman Verma (International Journal of Engineering and Management Research, 2020)
Replication protein A (RPA) is a single-stranded binding protein. RPA homologues have been identified in all eukaryotic organisms examined and are all abundant heterotrimeric proteins composed of subunits of approximately 70, 30, and 14 kDa. RPA required in DNA metabolism including DNA repair, recombination and DNA replication When RPA is bound to single- stranded DNA, it is phosphorylated by DNA- dependent protein kinase.